Integrasi Sensor Elektroanalitik dan Kecerdasan Buatan dalam Pengawasan Pencemaran Industri: Analisis Bibliometrik 1998–2024 - Nofriandi, Alwi; Yulkifli, Yulkifli; Dewata, Indang; Yohandri, Yohandri (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
The integration of electroanalytical sensors with artificial intelligence (AI) technology is increasingly becoming a major focus in the development of real-time and accurate industrial pollution monitoring systems. This study uses a bibliometric approach to analyze publication trends, journal sources, authors, and research topics related to voltammetry, impedimetry, and AI sensors in the context of industrial environmental quality monitoring during the period 1998–2024. The analysis results reveal a significant increase in the number of publications and citations since 2019, with the journals Sensors and Biosensors as the main publication channels. Prominent authors and emerging topics such as the use of artificial neural networks mark rapid progress in this field. However, there is still a need for the development of multifunctional sensors, IoT system integration, and more adaptive AI algorithms. This study emphasizes the urgency of further research with a multidisciplinary approach to support sustainable, efficient, and environmentally friendly industrial pollution monitoring.